Correlation of Arterial Stiffness and Bone Mineral Density by Measuring Brachial-Ankle Pulse Wave Velocity in Healthy Korean Women - Kim, Nam-Lee; Suh, Heuy-Sun (Korean journal of family medicine, 2015)
An association between arterial stiffness and osteoporosis has previously been reported. Therefore, we investigated the relationship between arterial stiffness, measured by brachial-ankle pulse wave velocity, and bone mineral density in a sample of healthy women undergoing routine medical checkup. We retrospectively reviewed the medical charts of 135 women who had visited the Health Promotion Center (between May 2009 and December 2012). Brachial-ankle pulse wave velocity was measured using an automatic wave analyzer. Bone mineral density of the lumbar spine (L1-L4) and femur was measured by dual-energy X-ray absorptiometry. Metabolic syndrome was defined according to National Cholesterol Education Program-Adult Treatment Panel III criteria, using body mass index >25 kg/m(2) instead of waist circumference >88.9 cm. Pearson's correlation analysis revealed significant inverse relationships between pulse wave velocity and bone mineral density of the lumbar spine (r=-0.335, P<0.001), femur neck (r=-0.335, P<0.001), and total femur (r=-0.181, P=0.04). Pulse wave velocity showed the strongest association with age (r=0.586, P<0.001). Multiple regression analysis identified an independent relationship between pulse wave velocity and lumbar spine bone mineral density in women after adjusting for age, metabolic syndrome, body mass index, smoking status, alcohol intake, and exercise (r=-0.229, P=0.01). This study confirmed an association between arterial stiffness and bone mineral density in women.